How to perform a cost management in the hotel sector for the best decision making? - Suárez, María Macarena (Unidad Editorial UPTC, 2020)
The objective of this work is to know alternatives of how to manage the companies of the hotel sector, emphasizing in the costing system of the same and the main activities, in this way the value of the services provided can be established more effectively. For this, the methodology to be used is a critical reading of specialized bibliography and through its study, adapt the activity cost management model to the hotel sector. The prevailing changes that have occurred in the environment as a consequence of globalization, increase in information technologies, internationalization of markets, have caused them to be distorted throughout the field, generating modifications in the concepts handled within organizations, in internal relations, in the management of human resources, and in the monitoring of processes. The results addressed in this report are the preparation of a phase manual to apply a cost system. In conclusion, you must know management accounting, since it will be very useful when formulating the entity's strategy, evaluating, evaluating, the budget that will be made for that and also to set prices, betting on a competitive advantage over various competitors. Keywords: Costs, off-book systems, management reports, ABM, ABC. JEL Codes: M150, G1 Received: 07/02/2019. Accepted: 28/04/2020.  Published: 24/05/2020